Geography of public finance: welfare under fiscal federalism and local government finance - Bennett, R. J. (London, 1980)
Part 1 of this book seeks to clarify the concept of a public good, its relationship to political economy, and the degree to which the functions of public finance must be tackled at a geographical as well as at a personal level. Part 2 of this book (chapters 5 to 10) treats the problem of fiscal equity over space through each of its aspects: of needs, revenue burdens, revenue incidence, benefit incidence, and the capital account. Part 3 analyses the forms of intergovernmental co-ordination required to achieve fiscal equity over space: especially important is the consideration of tax separation, grants and revenue-sharing. Chapter 14 draws each of these elements of the argument together and yields assessments of the final impact of fiscal incidence on the individual or firm. This discussion includes treatment of regional industrial policy and regional balance of payments accounts. Chapter 15 combines these conclusions with consideration of the influence of the political pork-barrel and log-rolling. The discussion employs extensive example material from the UK, the USA, Canada, Australia and Germany. The end product of the discussion is a general methodology for the geography of public finance which follows six stages: need assessment, cost measurement, determination of revenue capacity, measurement of revenue burden, assessment of benefit incidence, and determination of the appropriate levels of intergovernmental transfers.
Keywords: Finance, Public